KAJIAN HUKUM PIDANA TERHADAP GRATIFIKASI SEKSUAL SEBAGAI TINDAK PIDANA KORUPSI - Tua Raja Marpaung; Jaminuddin Marbun; Maurice Siburian (JURNAL PROINTEGRITA, 2021)
Sexual gratification as a criminal act of corruption is widely discussed in discussion forums in Indonesia. It has to do with how difficult it is to prove it. It is a Criminal Law Study of Sexual Gratification as a Corruption Crime. The problem formulations are: 1) Can sexual gratification be linked as a criminal act of corruption?; 2) How can the proof of the wrongdoing of the recipient of sexual gratification be a criminal act of corruption. The research method used is the normative juridical legal research method. The conclusions of this study are: 1) The crime of sexual gratification is a criminal act of corruption; 2) It is very difficult to prove the recipient of sexual gratification as a criminal act of corruption